2010
DOI: 10.1007/s12594-010-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on groundwater recharge potentiality of Barind Tract, Rajshahi District, Bangladesh using GIS and Remote Sensing technique

Abstract: The groundwater recharge potentiality in Barind Tract in Rajshahi district, Northwest Bangladesh was studied based on Geographical Information System (GIS) and Remote Sensing technique. In this connection satellite images (Landsat 7 ETM and SPOT) and aerial photos were subjected to several treatment processes using softwares like ERDAS Imagine and ESRI's Arc View. Thus various thematic maps have been prepared for drainage density, lineaments, lithology and land cover/use that allowed deciding their interactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Recently, there have been many studies focused on mapping MAR suitability, with special emphasis on using GIS to synthesize various surface and subsurface attributes that provide a means of ranking areas useful for MAR [ Saraf and Choudhury , ; Murray et al ., ; Ghayoumian et al ., ; Adham et al ., ; Russo et al ., ]. As indicated in these studies, MAR mapping is an important first step in developing MAR projects.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, there have been many studies focused on mapping MAR suitability, with special emphasis on using GIS to synthesize various surface and subsurface attributes that provide a means of ranking areas useful for MAR [ Saraf and Choudhury , ; Murray et al ., ; Ghayoumian et al ., ; Adham et al ., ; Russo et al ., ]. As indicated in these studies, MAR mapping is an important first step in developing MAR projects.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have suggested the presence of these features in the northern CV (Meirovitz 2010;Shlemon 1967), compelling further study of MAR dynamics in this system. Several studies have focused on synthesizing MAR suitability characteristics from a combination of spatial data, including remote-sensed imagery, geologic maps, and soil surveys to identify favorable surface site characteristics for MAR in CA (O'Geen et al 2015), and elsewhere (Adham et al 2010;Ghayoumian et al 2007). These studies provide a valuable initial survey of site suitability, but do not account for deeper subsurface geologic heterogeneity that has been shown to be important for recharge (e.g., Weissmann et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3) following Theissen Polygon method in such a way that each polygon is under influence of a single observation well [3]. Specific yield has been calculated for different polygons from the borelogs within the same polygon [4,5].…”
Section: Methods Of Studymentioning
confidence: 99%